High School EFL Teachers’ Continuous Professional Development: Target Needs, Reflection, And Challenges - Eshete, Mulualem; Gezahegn, Girma (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2022)
This research investigated the high school EFL teachers’ continuous professional development target needs, reflection, and challenges. Further, the target needs of the EFL teachers were analyzed by adapting Hutchinson & Waters’ model (1987). The data were collected using a test, questionnaire (consisting of five parts), and interview; these were administered to 20 high school EFL teachers. A test was administered to identify EFL teachers' present situation and difficulties, and questionnaire parts 1, 2, and 4 dealt with the EFL teachers' difficulties, needs, and purposes in the program. Moreover, these were used to identify EFL teachers’ target needs centered on their lack, necessities, and want to function effectively in the target situation. Parts 3 and 5 concerned high school EFL teachers' reflections and challenges in the professional development program they are involved in. Additionally, interviews were conducted with the high school EFL teachers to gather data to examine in-depth results of the target needs, reflections, and challenges. The results suggested that high school EFL teachers have different views of their lacks, wants, and necessities. The findings also demonstrated that the high school EFL teachers reflected that the current professional development program practiced in their school was never conducted to help EFL teachers develop their profession. Finally, the result revealed that high school EFL teachers face various challenges in their current program. Therefore, professional development should be revised according to EFL teachers’ target needs, reflections and challenges.